Actores en la vía: el Chaplin del sur de Cali: Observación sobre una actuación en el semáforo de la calle Quinta, entre los centros comerciales Unicentro y Holguines en Santiago de Cali (REVISTA NODO, 2009)
This article is the product of a monographic study that depicts the results of an ethnographic examination conducted in Santiago de Cali’s fifth street South during the course of a few months, which purpose was knowing, interacting andanalyzing a distinguishing phenomenon occurring in the publicspace: the South Chaplin’s performance. The power of the representation as well as the comprehensible acting of thecharacter allowed the researchers to recognize the dynamics that Richard Senett and Erving Goffman have theorized around observation and urban micro-sociology.
Keywords: Street expressions; city-characters; public performances, urban micro-sociology